2021
DOI: 10.1002/smll.202102567
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Identification of Single Mononucleotides by Nanoscale Electrophoresis

Abstract: amounts of input material. [1,2] While the sequencing-by-synthesis technology dominates currently, this technology requires significant sample preparation and amplification steps, the use of costly biological reagents such as fluorescently labeled molecules, and expensive imaging and data handling instruments. [3][4][5][6][7] Singlemolecule sequencing, which does not require amplification and labeling steps, would simplify the entire sequencing process significantly reducing costs and time of acquiring sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Excitingly, our findings are in good agreement with the experimental report by Choi et al , who also found a broad distribution when monitoring the TOF of dGMP by 5 μm nanochannel electrophoresis, but did not identify the reason. 37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excitingly, our findings are in good agreement with the experimental report by Choi et al , who also found a broad distribution when monitoring the TOF of dGMP by 5 μm nanochannel electrophoresis, but did not identify the reason. 37…”
Section: Resultsmentioning
confidence: 99%
“…The pattern of the electrophoretic migration velocity of nucleotides along the electric field direction is dTMP 4 dCMP 4 dAMP 4 dGMP, which is in agreement with experimental data. 37 Through the analyses, we found optimized electric field strengths of 0.7-0.8 V nm À1 which show considerably high identification accuracy among the four nucleotides. In addition, we found significant differences in the velocities corresponding to the two adsorption conformations of dGMP leading to the largest spreading of the signal in time, which explains the same experimental phenomenon.…”
Section: Introductionmentioning
confidence: 87%
“…We determined the average width of the current transient events at half-height and the average event amplitudes at voltages of 1 and 5 V. For these measurements, the current transients were measured using an in-house built current transimpedance amplifier (TIA) with the XnCC containing Ag/AgCl electrodes for recording electrical signals at the appropriate applied voltage. 28 Figure 3B shows a representative RPS data trace distributed over 100 s in 1× PBS blank and in Figure 3C is shown an expanded region (0.01 s); applied voltage = 1 V. An event was scored only if it had >1 data point per peak, an amplitude greater than a selected threshold, and a half-width ≥0.02 ms. As seen, the 1× PBS buffer resulted in no events exceeding the threshold.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…25 Afterward, Choi et al reported that the distance between two nanopores could influence the separation accuracy of molecules with different mobilities, showing an optimized length of 10 mm to discriminate four deoxynucleotide monophosphates. 26 These dual nanopore TOF sensors are actually a nanopore series circuit, while parallel nanopores are examined as well, termed ''Tug-of-War''. Zhang et al first fabricated this ''Tug-of-War'' nanofluidic device and reported its two features: (i) sensing and resensing the same DNA molecule in sequence by two independent nanopores; (ii) cocapture of one DNA molecule by two nanopores and significantly extending the translocation time.…”
Section: Introductionmentioning
confidence: 99%